2020
DOI: 10.20944/preprints202008.0406.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal Increase in D614G Mutation of SARS-CoV-2 in the Middle East and North Africa: Phylogenetic and Mutation Analysis Study

Abstract: Phylogeny construction can help to reveal evolutionary relatedness among molecular sequences. The spike (S) gene of SARS-CoV-2 is the subject of an immune selective pressure which increases the variability in such region. This study aimed to identify mutations in the S gene among SARS-CoV-2 sequences collected in the Middle East and North Africa (MENA), focusing on the D614G mutation, that has a presumed fitness advantage. Another aim was to analyze the S gene sequences phylogenetically. The SARS-CoV-2 S gene … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The D614G was found to be the second-highest mutation with a frequency of 92.6% (87/94) in our study. Sallam et al (2020) showed that the D614G mutation appeared to be taking over COVID-19 infections in the Middle East and North Africa (MENA) region as a significant increase in the proportion was noticed from 63.0% in February 2020 to 98.5% in June 2020 (p < 0.001). Two large phylogenetic clusters were identified through the ML analysis, which showed the evidence of intercountry mixing of sequences dating back to February 8, 2020 and March 15, 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The D614G was found to be the second-highest mutation with a frequency of 92.6% (87/94) in our study. Sallam et al (2020) showed that the D614G mutation appeared to be taking over COVID-19 infections in the Middle East and North Africa (MENA) region as a significant increase in the proportion was noticed from 63.0% in February 2020 to 98.5% in June 2020 (p < 0.001). Two large phylogenetic clusters were identified through the ML analysis, which showed the evidence of intercountry mixing of sequences dating back to February 8, 2020 and March 15, 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The current coronavirus disease 2019 (COVID-19) pandemic does not seem to show any signs of decline, with more than 1.7 million deaths and more than 80 million reported cases worldwide, as of 27 December 2020 [ 29 , 30 ]. The ebb and flow of COVID-19 cases can be driven by human factors, including attitude towards physical distancing and protective measures, while viral factors are driven by mutations that commonly occur in severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) genome [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The viral factors can particularly be of high relevance considering the recent reports of resurgence in COVID-19 infections in UK due to a new variant of the virus [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current coronavirus disease 2019 (COVID-19) pandemic does not seem to show any signs of decline, with more than 1.7 million deaths and more than 80 million reported cases worldwide, as of December 27, 2020 [11,12]. The ebb and flow of COVID-19 cases can be driven by human factors including attitude towards physical distancing and protective measures, while viral factors are driven by mutations that commonly occur in severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) genome [13][14][15][16][17][18]. The viral factors can be particularly of high relevance considering the recent reports of resurgence in COVID-19 infections in UK due to a new variant of the virus [19].…”
Section: Introductionmentioning
confidence: 99%